The Image of Oscar Wilde in Film - Stěhulová, Pavla (Univerzita Pardubice, 2025)
This thesis focuses on the portrayal of Oscar Wilde and related concepts of Conformity, Sexuality, and Family in biographical films about his person. The films were chosen to represent different time periods in contemporary history. Background on Conformity, Sexuality, and Family in the context of the Victorian era is given in the theoretical chapters of the thesis. Following, the films are analysed with emphasis on changes in the described themes and the focus on them in the chosen films. The progress in portraying the themes is tracked, and the thesis is closed with a final chapter which recapitulates, compares, and derives general conclusions from the analysis.
Obraz Oscara Wildea ve filmovém zpracování
Keywords: conformity; scandal; sexuality; homosexuality; family; nuclear family; biography; Wilde, Oscar; Victorian era; konformita; skandál; sexualita; homosexualita; rodina; nukleární rodina; biografie; Wilde, Oscar; viktoriánská doba